Positive parenting style and positive health beyond the authoritative: Self, universalism values, and protection against emotional vulnerability from Spanish adolescents and adult children - Palacios, Iria; Garcia, Oscar F.; Alcaide, Marta; Garcia, Fernando (Frontiers in Psychology, 2022)
Introduction Recent research is fully questioning whether the combination of parenting warmth and strictness (the authoritative style) is always identified as positive parenting across the globe. This study analyzes parenting styles and the positive health of adolescents and adult children. Methods The sample was 2,090 Spanish children (59.9% women), from four age groups: 600 adolescents, 591 young adults, 507 middle-aged adults, and 392 older adults. Parenting styles (indulgent, authoritative, authoritarian, and neglectful) were obtained by warmth and strictness measures. Children’s positive health was measured by self (family self-concept, self-esteem, and negative self-efficacy), universalism values, and emotional vulnerability. Results The main results showed that the indulgent parenting style was associated with equal and even better scores than the authoritative style, whereas the authoritarian and neglectful styles were consistently associated with low scores in positive health indicators for all age groups. However, two triple interactions of sex by age group by parenting style showed that women children from neglectful families reported the lowest family self-concept in old age and the highest emotional vulnerability in middle age. Discussion The study findings question the universal benefits of the so-called positive parenting (the authoritative style) for positive health.